Role of cardiac dyssynchrony and resynchronization therapy in functional mitral regurgitation. (European Heart Journal - Cardiovascular Imaging, 2016)
Functional mitral regurgitation (FMR) is a common complication of left ventricle (LV) dysfunction and remodelling. Recently, it has been recognized as an independent prognostic factor in both ischaemic and non-ischaemic LV dysfunctions. In this review article, we discuss the mechanisms through which cardiac dyssynchrony is involved in FMR pathophysiologic cascade and how cardiac resynchronization therapy (CRT) can have therapeutic effects on FMR by reverting specific dyssynchrony pathways. We analyse recent clinical trials focusing on CRT impact on FMR in 'real-world' patients, the limits and future perspectives that could eventually generate new predictors of CRT response in terms of FMR reduction. Finally, we propose a practical diagnostic and therapeutic strategy for the management of symptomatic patients with severe LV dysfunction and concomitant 'prognostic' FMR.